Maternal perceptions of the experience of attempted labor induction and medically elective inductions: analysis of survey results from listening to mothers in California - Declercq, Eugene (BMC Pregnancy Childbirth, 2020)
BACKGROUND: The rate of induction of labor in the U.S. has risen from 9.6% in 1990 to 25.7% in 2018, including 31.7% of first-time births. Recent studies that have examined inductions have been small qualitative studies or relied on either medical records or administrative data. This study examines induction from the perspective of those women who experienced it, with a particular focus on the prevalence and predictors of inductions for nonmedical indications, women’s experience of pressure to induce labor and the relationship between the attempt to medically initiate labor and cesarean section. METHODS: Study data are drawn from the 2119 respondents to the Listening to Mothers in California survey who were planning to have a vaginal birth in 2016. Mothers were asked if there had been an attempt to medically initiate labor, if it actually started labor, if they felt pressured to have the induction, if they had a cesarean and the reason for the induction. Reasons for induction were classified as either medically indicated or elective. RESULTS: Almost half (47%) of our respondents indicated an attempt was made to medically induce their labor, and 71% of those attempts initiated labor. More than a third of the attempts (37%) were elective. Attempted induction overall was most strongly associated with giving birth at 41+ weeks (aOR 3.28; 95% C.I. 2.21–4.87). Elective inductions were more likely among multiparous mothers and in pregnancies at 39 or 40 weeks. The perception of being pressured to have labor induced was related to higher levels of education, maternal preference for less medical intervention in birth, having an obstetrician compared to a midwife and gestational ages of 41+ weeks. Cesarean birth was more likely in the case of overall induction (aOR 1.51; 95% C.I. 1.11–2.07) and especially following a failed attempt at labor induction (aOR 4.50; 95% C.I. 2.93–6.90). CONCLUSION: Clinicians counselling mothers concerning the need for labor induction should be aware of mothers’ perceptions about birth and engage in true shared decision making in order to avoid the maternal perception of being pressured into labor induction.